2017
DOI: 10.12957/reuerj.2017.15133
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento dos diagnósticos, resultados e intervenções de enfermagem de uma unidade oncológica [Mapping of nursing diagnoses, results and interventions in an oncology unit]

Abstract: RESUMO Objetivo: identificar os principais diagnósticos, intervenções e resultados de enfermagem descritos pela North American Nursing Diagnosis Association (NANDA), Nursing Outcomes Classification (NOC), Nursing Intervention Classification (NIC), para pacientes oncológicos internados. Método: estudo com abordagem quantitativa, transversal, realizado entre março a outubro de 2014, na unidade de oncologia de um hospital filantrópico, localizado no sul do estado da Bahia. A amostra foi de 157 pacientes, os dados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
5
0
6
Order By: Relevance
“…Seven clinical indicators for children and adolescents with cancer in our study predicts the presence of this nursing diagnosis, and it was the most prevalent in this study: discomfort, discontent with situation, unease in situation, irritability, crying, feeling cold, and fear. Similar studies in an oncology inpatient unit (adult and paediatric) also identified a high prevalence of these clinical indicators (Leandro et al, 2018; Silva et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Seven clinical indicators for children and adolescents with cancer in our study predicts the presence of this nursing diagnosis, and it was the most prevalent in this study: discomfort, discontent with situation, unease in situation, irritability, crying, feeling cold, and fear. Similar studies in an oncology inpatient unit (adult and paediatric) also identified a high prevalence of these clinical indicators (Leandro et al, 2018; Silva et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
“…Similar studies in an oncology inpatient unit (adult and paediatric) also identified a high prevalence of these clinical indicators (Leandro et al, 2018;Silva et al, 2017).…”
Section: Seven Clinical Indicators For Children and Adolescents With ...mentioning
confidence: 52%
See 2 more Smart Citations
“…No processo perioperatório, os enfermeiros tendem a direcionar os pacientes não somente na compreensão do tratamento e enfretamento de possíveis mudanças, mas emocionalmente, mediante ao suporte na expressão moral dos seus valores, realizando assim a consolidação do vínculo de confiança frente ao amparo as dificuldades inerentes ao momento (FRUET IMA, et al, 2017). Além destas condutas poderem contribuir com a melhorar a qualidade de vida das pessoas com câncer (Silva MR et al, 2017).…”
Section: Discussionunclassified